Innovative use of Reinforced Concrete for Sustainability of Purse Seine Boat Building in Aceh. (2015) - Triastuti, Nusa Setiani; Soewarno, Noraya
Abstract: Indonesia is an archipelago with only 30% landmass, hence inter-island transport and fisheries are important sectors. Boats used by fishermen and to transport goods as well as people across Indonesia's many islands are mainly small to medium sized timber boats of up to 30 gross weight tonnes (GWT). Large sized timber beams are needed for the boat keel and frames. However, since 2007 logging was banned in the Nanggroe Aceh Darusalam (NAD) region. This has resulted in scarcity and increased timber costs for conventional timber boat builders in the area. Hence other suitable substitute materials, in lieu of timber, should be explored to build fishermen's purse seine boats. In this study, we explore an innovative use of reinforced concrete as substitute for large size timber keel and boat hull frames of purse seine fishermen boats. As far as we are aware, this type of exploration study specific for purse seine boats in NAD is unprecedented. Our analysis indicates that using concrete frame provides better stability and adds to the boat's strength as well as extends its life use. Further, reinforced concrete can be a more cost efficient material to substitute for boat timber frame. Leaner reinforced concrete beams can be used compared to timber beams. The cost savings of using concrete for the boat frame in lieu of timber frame is estimated to be around 15%. Construction time to build a boat using reinforced concrete frame can be reduced by almost half compared to conventional timber frame boat of the same size. The findings of this exploratory study can contribute to enrich innovations in civil engineering construction, sustain the traditional purse seine boat building industry, and ultimately the livelihood of fishermen in NAD region. Findings can also be potentially further explored for application to other type of traditional timber boat construction for inter-island sea transportation services of goods and people in Indonesia, and perhaps also for other archipelago developing nations as well.